GC-MS ANALYSIS OF PHYTOCOMPONENTS IN THE ETHANOLIC EXTRACT FROM WHOLE PLANT OF LACTUCA RUNCINATA DC. - Devi, JEYARAMAN AMUTHA ISWARYA; Kottai Muthu, Arumugam (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The objective was to characterize the phytochemical constituents in ethanolic extract from the whole plant of Lactuca runcinata DC. by gas chromatography-mass spectrometry (GC-MS). Methods: The shade-dried whole plant powder was extracted with ethanol using Soxhlet extractor and crude extract was used for GC-MS. Results: The GC-MS analysis was used to determine the presence of 20 different phytochemical compounds in the ethanolic whole plant extract of L. runcinata, showed that they were different types of high and low molecular weight compounds. Conclusions: This GC-MS study helps to predict the formula and structure of phytoconstituents and which can be used as drugs, and further investigation may lead to the development of drug formulation. Keywords: Ethanolic extract, Gas chromatography-mass spectrometry analysis, Lactuca runcinata DC., Phytocomponents.